Youngest Cretaceous dinosaur tracksite from the Middle East (Maastrichtian, Farrokhi Formation, Central Iran) - Wilmsen, Markus; Fürsich, Franz; Majidifard, Mahmoud Reza (Palaeobiodiversity and Palaeoenvironments, 2021)
A late early Maastrichtian dinosaur trampling site is reported from the Farrokhi Formation of the Khur area, Central Iran. The largely indeterminate footprints, some of which may represent undertracks, can be classified as natural moulds (i.e. concave epireliefs) bordered by a raised rim of displaced sediment. They reach diameters of up to 0.5 m and were impressed under very shallow to subaerial conditions in an inter- to supratidal environment. Two generations of traces have been imprinted, initially into a soft, fine-grained carbonate sand and afterwards into a superficially hardened substrate that was still plastic underneath; the change in substrate consistency is supported by a conspicuous cracking pattern around the footprints. As a result, hardly any details of the foot morphology of the trackmakers are recorded. Nevertheless, the occurrence improves our knowledge about dinoturbation and its preservation in different kinds of substrates. Furthermore, it is the youngest record (ca. 70 Ma) of dinosaur locomotion traces from Iran and, in all probability, the entire Middle East.
CRIS-Team Scopus Importer:2021-12-17
Keywords: Composite surface; Dinoturbation; Emersion; Late Cretaceous; Tidal flats; Yazd Block